Redesign User Interface (UI) and User Experience (UX) of Ikan Giling Segar Website with Design Thinking Method to Increase User Interest - Husniyah, Nadiyah; Guntara, Rangga Gelar; Jaelani, Rusani (Universitas Negeri Padang, 2024)
In this era, digital transformation in business is increasing. One of the businesses that participated in the transformation and was studied in this research is Sabrina Store, which sells groundfish through its website, Ikan Giling Segar. Even so, challenges arise related to website design that is not optimal. This research is included in the Research and Development (R&D) research type. It uses design thinking methods to improve the appearance of the website design so that user interest also increases. Data were collected through questionnaires and related literature. Pre-questionnaires and questionnaires were conducted after the redesign using the User Experience Questionnaire (UEQ) method with respondents from potential users in East Java, as well as usability testing of the redesigned prototype. Results showed that five aspects of UEQ were below average before the redesign. However, after the redesign, all aspects improved. Usability and UEQ testing also showed that the redesign improved user interest and experience. Thus, using design thinking and R&D methods can provide holistic solutions to improve the UI / UX of online business websites with positive results.